2016
DOI: 10.1111/jpm.12294
|View full text |Cite
|
Sign up to set email alerts
|

Worker, workplace or families: What influences family focused practices in adult mental health?

Abstract: Accessible summaryWhat is known on the subject?• Family focused practice leads to positive outcomes for parents and children.• There are barriers and enablers for practitioners being family focused.What this paper adds to existing knowledge?• Worker skill, knowledge and confidence about family work are the most important factors associated with family focused practices.What are the implications for practice?• Mental health nurses require specific skill training in family focused practices, time to engage with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
82
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(93 citation statements)
references
References 35 publications
8
82
3
Order By: Relevance
“…Most ( N = 200, 87%) of social workers in this study also had no training to support mothers, beyond those with perinatal mental illness. While others have also found that limited skill and knowledge and training hinder mental health professionals’ capacity to engage in FFP (Grant et al, ; Maybery, Goodyear, Reupert, & Grant, ; Tungpunkom et al, ), this study suggests that health visitors have different needs in relation to training than other professionals. For instance, while they may have knowledge and skills to support children, they have deficits in knowledge and skill in relation to supporting mothers with severe mental illness.…”
Section: Discussioncontrasting
confidence: 51%
“…Most ( N = 200, 87%) of social workers in this study also had no training to support mothers, beyond those with perinatal mental illness. While others have also found that limited skill and knowledge and training hinder mental health professionals’ capacity to engage in FFP (Grant et al, ; Maybery, Goodyear, Reupert, & Grant, ; Tungpunkom et al, ), this study suggests that health visitors have different needs in relation to training than other professionals. For instance, while they may have knowledge and skills to support children, they have deficits in knowledge and skill in relation to supporting mothers with severe mental illness.…”
Section: Discussioncontrasting
confidence: 51%
“…Similarly, Maybery et al . () found that knowledge and skill was a key predictor of Australian mental health professionals’ FFP and recommended that they receive training in FFP to support parents, children, and adult family members. When nurses report adequate knowledge and skills, they perceive fewer barriers to FFP and are more likely to engage (Grant et al .…”
Section: Discussionmentioning
confidence: 99%
“…Maybery et al . () found that professionals’ knowledge and skill was the most important predictor of FFP. Goodyear et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, empirical investigation of this model suggested that factors relating to clinicians, such as their attitude, confidence, and skill, were better predictors of family-focused practice than the other levels (Maybery, Goodyear, Reupert, & Grant, 2016). Although it is important to identify the barriers of family-focused practice, it is arguably more important to consider how these barriers might be addressed.…”
mentioning
confidence: 99%